THE EFFECT OF LEADERSHIP STYLE AND COMPENSATION ON VILLAGE OFFICE PERFORMANCE WITH WORK MOTIVATION AS A MEDIATING VARIABLE IN SEVERAL VILLAGES IN MANTUP DISTRICT - Achmad Reza; Rifky Ardhana Kisno Saputra; Ahmad Fathur Rozi (RADJA PUBLIKA, 2026)
Abstract. This study aims to find empirical evidence whether leadership style and compensation influence performance through motivation on village officials in several villages in Mantup District. This study uses a quantitative type with an explanatory approach. The study uses primary data collected directly. The population is all village officials in Mantup District, with a purposive sampling technique obtained a sample of 36 village officials working in Kedungsoko, Rumpuk, and Sumberbendo Villages, namely villages that have problems related to the performance of their village officials. Data were collected using a questionnaire technique, and processed using path analysis with the help of SmartPLS which consists of an evaluation of the measurement model to prove the instrument is valid and reliable; and an evaluation of the structural model to prove the research hypothesis. The results of the study concluded that leadership style is a significant predictor that positively influences work motivation and performance of village officials. However, compensation is unable to influence work motivation or performance of village officials. Work motivation is able to be a significant predictor that positively influences performance. Keywords: Leadership Style; Work Performance; Compensation; Work Motivation; Village Apparatus.